Biogeochemistry of phytoplankton RuBisCO in the ocean - Thornton, Daniel C. O. (Frontiers in Marine Science, 2025)
Form I Ribulose-1,5-bisphosphate oxygenase/carboxylase (RuBisCO) is the most abundant enzyme on Earth, playing a key role in carbon fixation during oxygenic photosynthesis. Using published sequence data, I show that there are significant differences in the amount of elemental resources (C, N and S) and energy required to synthesize the different Types of Form I RuBisCO. The shorter amino acid lengths of cyanobacterial RuBisCO had lower resource requirements to build the holoenzyme compared with eukaryotes. Consequently, the rise to dominance of eukaryote phytoplankton during the Neoproterozoic (1000–541 Ma) led to a shift to more expensive eukaryote RuBisCO. There are also significant differences in the elemental composition of RuBisCO between eukaryotes in different supergroups. Estimates of resource allocation were used to estimate how much C, N and S is associated with RuBisCO in the modern ocean. The marine cyanobacterium Prochlorococcus is the most numerically abundant photosynthetic organism on Earth and accounts for 7.3 – 8.9% of net ocean primary productivity. There are 2.11- 2.69 x 106 mol RuBisCO in Prochlorococcus, which amounts to 4 to 5% of the total RuBisCO pool in the ocean. The relatively low RuBisCO content compared with productivity indicates highly efficient photosynthesis in Prochlorococcus. The total marine RuBisCO reservoir is equivalent to 0.016 Pg C, 5.1 Tg N, and 0.4 Tg S. The estimated annual productivity of RuBisCO is equivalent to 0.725 - 0.890 Pg C yr-1, 228–283 Tg N yr-1, and 16.5 - 22.5 Tg S yr-1. In the context of the marine nitrogen cycle, the amount of nitrogen fluxing through the pool of RuBisCO each year is equivalent to, or even higher, than the rate of biological nitrogen fixation (223 ± 30 Tg N yr−1). Turnover of RuBisCO is rapid, occurring every 6.6 to 8.2 days. In conclusion, RuBisCO is not only significant as the primary carbon fixation enzyme in the ocean, but also as a pool of chemical elements, particularly nitrogen.